Skin manifestations associated with systemic diseases - Part I, - Ana Luisa Sampaio; Aline Lopes Bressan; Barbara Nader Vasconcelos; Alexandre Carlos Gripp (Sociedade Brasileira de Dermatologia, 2022)
Abstract The skin demonstrates what is happening in the body in many diseases, as it reflects some internal processes on the surface. In this sense, skin as an organ, goes beyond its protective and barrier functions, as it provides clues for the identification of some systemic diseases. The dermatologist then raises diagnostic hypotheses for conditions related to all systems and refers them to the appropriate specialty. With easy access to examination by trained eyes and biopsies, the skin can present specific or non specific alterations on histopathology. In the first case this combination establishes the diagnosis of the disease itself. Non specific manifestations can occur in a variety of contexts and then histopathology is not specific of a particular disease. This article is divided into two parts that will cover large groups of diseases. In this first part, cutaneous manifestations of the main rheumatologic diseases are described, which are the ones with the greatest interface with dermatology. The authors also talk about vascular manifestations and granulomatous diseases. In the second part, endocrinological, hematological, oncological, cardiovascular, renal, gastrointestinal diseases, pruritus and its causes are discussed, and finally, the dermatological manifestations of SARS-CoV-2 coronavirus infection. The authors' intention is that, by using direct and easily accessible language, aim to provide practical material for consultation and improvement to all dermatologists who recognize the importance of a comprehensive assessment of their patients.